THE INFLUENCE OF SCHOOL PRINCIPALS' SITUATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON TEACHER WORK MOTIVATION - NAWARDA, Faizin; FITRIANI, Somariah; WAHJUSAPUTRI, Sintha (Journal of Education and Leadership in Education, 2023)
The purpose of this research is to analyze and test: (1) The influence of the principal's situational leadership on teacher work motivation. (2) The influence of organizational culture on teacher work motivation, (3) The influence of the principal's situational leadership on organizational culture. This research is a quantitative survey type research. The population in this study were all teachers in Pancoran District Public Elementary Schools, South Jakarta, with a sample of 124 teachers taken at random (random sampling). The analysis technique used is the path analysis technique. The results of this research show that (1) There is no significant influence of the Principal's Situational Leadership on the Work Motivation of Public Elementary School Teachers in Pancoran District, South Jakarta. (2) There is a direct positive and significant influence of Organizational Culture on the Work Motivation of Public Elementary School Teachers in Pancoran District, South Jakarta. (3) There is a direct positive and significant influence of the Principal's Situational Leadership on the Organizational Culture of Public Elementary Schools in Pancoran District, South Jakarta. The conclusion in this research is that to create teacher work motivation, the principal should understand follower behavior and the situation before using certain leadership behavior. The organizational culture in the school should be able to identify the characteristics of each teacher to create harmonious relationships between members of the school environment and provide mutual motivation between teachers.